Design and Implementation of Interactive Coding with Gamification for Web Programming Subject for Vocational High School Students - Arif, Rahadyan Fannani; Rosyid, Harits Ar; Pujianto, Utomo (2019 International Conference on Electrical, Electronics and Information Engineering (ICEEIE), 2019)
Students in vocational high schools majoring in software engineering programs are required to have web programming skills as one of the favourable demands in the industry today. However, there are lacking supports for learning such subjects in vocational high schools that can be offered from conventional methods. Hence, the students failed to understand and follow the instructions in the module. This study aims to develop a web application to comprehend web programming in an advanced way for students and engage them with gamification method. By combining ADDIE and Prototyping models the research obtained validation results 95.24% and 91.93% from education and media experts, respectively. Based on the small and large groups trials conducted at State Vocational High Schools 4 Malang, more than 87 per cent participants accepted the web application's feasibility. From these validations, it can be affirmed that the research product was valid and feasible to support the learning process of Basic Programming subjects in Vocational High School.